Strategic planning of the regional environmental policy - Chernyhivska Anna V. (Problemi Ekonomiki, 2014)
The article justifies the necessity of introduction of management of regional development of strategic planning. It focuses on importance of the complex work on creation of regulatory and legal, organisational and educational grounds of these activity and also availability of social and material motivation for this activity to become necessary, mandatory and sensitive. The article is devoted to theoretical, methodological and applied issues of formation and realisation of the regional environmental policy. It justifies theoretical essence of the “regional environmental policy” notion. It offers priority directions of the regional ecological policy. It shows that strategic planning of the regional development is based on assessment of competitive advantages and shortcomings of a region and also opportunities and threats with respect to its further development and is considered as one of the most prospective and efficient mechanisms of realisation of the long-term regional environmental policy under conditions of global integration.